2015
DOI: 10.1007/s00520-015-2953-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on cancer-related fatigue: a meta-analysis of randomized controlled trials

Abstract: Cancer patients can make more informed choices regarding their cancer-related fatigue management based on the best available evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 46 publications
7
110
1
5
Order By: Relevance
“…However, the other moderate GRADE meta-analysis58 that included only studies investigating aerobic exercise reported a pooled effect estimate (SMD: −0.22, 95% CI −0.39 to –0.04) that was similar to the remaining studies. One moderate GRADE meta-analysis57 included only studies investigating resistance exercise and reported a pooled effect estimate (SMD: −0.19, 95% CI −0.38 to 0.00) that tended to be smaller than the remaining studies.…”
Section: Resultsmentioning
confidence: 77%
“…However, the other moderate GRADE meta-analysis58 that included only studies investigating aerobic exercise reported a pooled effect estimate (SMD: −0.22, 95% CI −0.39 to –0.04) that was similar to the remaining studies. One moderate GRADE meta-analysis57 included only studies investigating resistance exercise and reported a pooled effect estimate (SMD: −0.19, 95% CI −0.38 to 0.00) that tended to be smaller than the remaining studies.…”
Section: Resultsmentioning
confidence: 77%
“…An exercise session would be only cancelled if a patient was experiencing fever (temperature > 38°C/100.4°F), low blood platelet levels (< 50.000 per μl), a neutrophil count lower than 500 cells per μl, marked anemia (hemoglobin < 8 g/dl) or severe cachexia (i.e., weight mass loss > 35%) [24]. Patients had participated in a supervised aerobic exercise program by one of the researcher (3 sessions /week with each session lasting from 20-40 minutes).…”
Section: Exercise Intervention Aerobic Exercisementioning
confidence: 99%
“…In recent years four reviews [51][52][53][54] have shown the positive effects of exercise on fatigue, including CRF during and after treatment and also on chronic fatigue syndrome. However, the reviews outlining the results must be interpreted cautiously due to the heterogeneity of exercise programs tested and measures used to assess the results.…”
Section: • • Physical Activitymentioning
confidence: 99%